Technical Success Level Analysis Hitting, Scoop and Reserve Hit Sport Hockey Outdoor on Eventmen’s Asian Games Qualifer 2022 - Nabilah, Tiara Sekar; Hariadi, Imam; Widiawati, Prisca (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
This study aims to determine the success and percentage of hits, scoop and reserve hits in the Hockey Outdoor Men's Asian Games Qualifer 2022 competition. The design of this study is a descriptive quantitative method using video analysis. The research subjects were 9 teams. The instrument used in this study was an analysis sheet by means of a video review. Data collection by non-test method using documentation techniques in the form of video analysis. Furthermore, the data will be sorted and analyzed using data descriptions. Based on the results of the research, hits in all Hockey Outdoor Men's Asian Games Qualifer 2022 matches obtained the highest percentage of 48% by the Sri Lankan national team, this result did not determine the team won the championship. The highest percentage of scoops obtained in the Hockey Outdoor Men's Asian Games Qualifer 2022 was 66% achieved by the Oman national team, with this result Oman was able to win 1st place. by the Singapore national team, these results could not lead the Singapore team to become champions because each team has a different strategy. Of the three techniques, the one with the highest percentage is the reserve hit because the success rate is higher than the failure rate.